Teacher's Strategies to Overcome Learning Difficulties Arabic Language Students of MAN III Sleman - Widita, Cintya Sukma (Utan Kayu Publishing, 2022)
This study aims to find out what learning difficulties experienced by students in learning Arabic subjects, knowing the teacher's strategies in overcoming learning difficulties of Arabic students in MAN III Sleman and knowing the effectiveness of teacher strategies in overcoming difficulties in learning Arabic Language MAN III students Sleman. This study uses a descriptive qualitative approach. The data collection techniques are observation, interviews and documentation, the analysis technique is analytical descriptive analysis, the method is data reduction and data display, then the data is collected in the form of observation, documentation, interviews. The results reveal that the learning difficulties of students studying Arabic subjects at MAN III Sleman are lack of understanding of sound/ashwat, grammar/mufrodat, sentence structure/qowa'id, meaning, lack of concentration, boredom during learning, lack of interest in learning. Arabic language and teacher attitude is not friendly. The teacher's strategy to overcome the difficulties of learning Arabic for students at MAN III Sleman includes students usually making a mandatory deposit of 15 vocabularies to the teacher, the teacher repeats the lesson, holds ice breaking, uses various media, provides motivation and conducts self-evaluation. The teacher is considered effective in overcoming the difficulties of learning Arabic for students at MAN III Sleman.